THU0060 Serum ykl-40 in rheumatoid arthritis: clinical correlations. (1st June 2001) - Carrabba, M; Chevallard, M; Torchiana, E; Puttini, PC Sarzi; Santandrea, S; Boccassini, L; Antivalle, M; Santalena, G; Marrazza, MG
Abstract : Background: YKL-40 or gpl-39 is a surface glycoprotein of connective tissue cells in particular of monocytes, fibroblasts, synoviocytes and chondrocytes. According to some Authors, being augmented in serum of rheumatoid arthritis (RA) and, to a lesser extent, of osteoarthritis (OA) it may correlate with the degree and the speed of cartilage degradation. Objectives: To better evaluate if this is true or if this marker is mainly an inflammation index, we have investigated a group of RA patients correlating YKL-40 serum values with some of the clinical parameters of the disease most widely used in literature (swollen or painful joint count, HAQ, PCR, Ra-test, ESR, Rx score of the hands, DAS 28). Methods: We have evaluated 52 consecutive patients (43 F, 9 M) with RA according to the ACR criteria mainly in the 2nd (22) or 3rd (25) functional class of Steinbrocker. Their mean age was 59.7 years (33–86) and the mean disease duration 13.6 years (1–35). The YKL-40 was determined in serum according to the ELISA sandwich method of Harvey et al, 1998 (normal range: 25–95 ng); all the patients (pts) were previously visited and all the parameters listed above measured. Moreover the Rx score of the hands was calculate according to the method of Kaye, 1987, slightly modified. The significance of the correlations were evaluated with the Spearman test. Results: The mean (± SD) serum values of YKL-40 was 147.84 (± 97.47) ng(normal range: 25–95 ng). The correlations with the parameters listed above were those shown in the following Table 1 . Swollen joint count, Rx score and Ra-test showed a still less significant correlation with the marker investigated. Conclusion: Since YKL-40 in RA serum seems to better correlate with PCR, DAS 28 and painful joint count respectively, in our opinion it behaves more like an activity marker of the disease (perhaps of synovitis) rather than of cartilage degradation as claimed by some Authors. Despite this limitation, further studies are needed to evaluate its potential prognostic activity as predictor of joint lesions in RA. References: Harvey S, et al. Chondrex: a new marker of joint disease. Clin Chem. 1998;44:509–16 Wollheim FA. Markers of disease in RA. Curr Opin Rheumatol. 2000;12:200–4